Bitemporal data : theory and practice - Johnston, Tom (Morgan Kaufmann, 2014)
Bitemporal data is coming, and major database management systems are beginning to support it. You need to know what is going on ""under the hood"" and this book that will make you the expert on bitemporal data that every IT organization should have on its staff. There''s a lot more to bitemporal data than adding a second timestamp to history tables: for example, a temporal update of a single customer in a bitemporal customer table could require up to a dozen physical SQL transactions to complete. Vendors will eventually make it possible to write bitemporal transactions and bitemporal queri.